2018
DOI: 10.1177/1750458918776551
|View full text |Cite
|
Sign up to set email alerts
|

Use of the WHO surgical safety checklist in low and middle income countries: A review of the literature

Abstract: A wealth of research now exists surrounding use of the WHO surgical safety checklist. This paper reviews the literature regarding checklist use in developing countries. Results identify a lack of available literature specific to developing countries despite this potentially being where the greatest impact could be observed. Unique challenges of checklist use are discussed and opportunities for future research focusing on use of the checklist in developing countries suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
(61 reference statements)
0
16
0
3
Order By: Relevance
“…This study extends previous implementation research in important ways. The scant research on implementation of surgery interventions often focuses on the active implementation phase (5,14,15,60), which may miss important insights into all the factors that drive success or failure in implementation (60). Second, studies applying the EPIS framework have largely focused on social services such as mental and behavioral health, substance use, and child welfare (27,(61)(62)(63) but, to date, none have examined surgical services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study extends previous implementation research in important ways. The scant research on implementation of surgery interventions often focuses on the active implementation phase (5,14,15,60), which may miss important insights into all the factors that drive success or failure in implementation (60). Second, studies applying the EPIS framework have largely focused on social services such as mental and behavioral health, substance use, and child welfare (27,(61)(62)(63) but, to date, none have examined surgical services.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of sufficient funding has an impact on surgical providers' ability to complete EBPs with completeness and fidelity. For example, studies in low-resource settings have found that adherence to the SSC may be affected by limited resources such as the lack of pulse oximeters for monitoring, antibiotics for prophylaxis, or markers for site marking (15,60,72). Another important decision during the Exploration phase was to have multi-partner leadership of SS2020 because no single organization could provide a holistic solution.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…No Brasil, as evidências científicas disponíveis abrangeram conhecimento, percepção e atitudes da equipe, adesão e impacto da LVSC 7,8 . Contudo os estudos desenvolvidos pouco exploraram o processo de implementação do checklist [6][7][8][9] .…”
Section: Introductionunclassified
“…Para defender continuamente a LVSC como medida de segurança cirúrgica aplicável à população global, a pesquisa nesses países precisa ser prioridade. As estratégias de implementação devem ser investigadas no contexto dos países em desenvolvimento para que os hospitais possam avaliar a abordagem mais adequada para introduzir o uso do checklist e mais compatível com a realidade local, a fim de promover o incremento da utilização dessa ferramenta e beneficiar mais pacientes 9 .…”
Section: Introductionunclassified
“…In a recent literature review, the authors stated that in low- and middle-income countries there is a lack of research on SSC compared to the large number of studies conducted in high-income countries that made it possible to construct a robust body of evidence in relation to use of the tool in practice. Although some of this knowledge can be applied and transferred to low- and middle-income countries, there are specific issues regarding the implementation and use of the checklist in the context of these countries, such as: the introduction of LSVC use in health services that did not incorporate and other relevant practices such as the surgical counting process, surgical site marking and administration of antibiotics, as well as limited resources and cultural differences 9 .…”
Section: Introductionmentioning
confidence: 99%